The development of a mouse model to explore resistance and susceptibility to early Ascaris suum infection - Lewis, Paul Ranjith (Trinity College (Dublin, Ireland). Department of Zoology, 2006)
Ascaris suum and Ascaris lumbricoides are widespread geohelminths of pigs and humans, respectively, resulting in severe morbidity and possible mortality. The contribution of migrating A. suum larvae to liver damage has been observed in pigs and is problematic, resulting in liver condemnation at slaughter. The larval stages of both species are also associated with allergic and respiratory symptoms and these are an understudied source of morbidity and mortality in people. Bronchovascular damage resulting from migrating larvae may produce secondary damage caused by opportunistic microorganisms. Furthermore, it is believed that susceptibility to the larval population may be a determinant factor in the development of a patent adult population. A. suum and A. lumbricoides exhibit an overdispersed frequency distribution in their host populations in both the adult and larval stages and individuals appear to be predisposed to either high or low intensities of infection. The impact of host factors on this observed distribution is still poorly understood and difficult to investigate in natural host populations particularly in relation to the larval stages. The use of a mouse model has been supported by the observations that the larval migratory pattern mimics the pattern observed in the pig.
Keywords: Zoology, Ph.D.; Ph.D. Trinity College Dublin